2015
DOI: 10.1097/ogx.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

A 9-Valent HPV Vaccine Against Infection and Intraepithelial Neoplasia in Women

Abstract: BACKGROUNDThe investigational 9-valent viruslike particle vaccine against human papillomavirus (HPV) includes the HPV types in the quadrivalent HPV (qHPV) vaccine (6, 11, 16, and 18) and five additional oncogenic types (31, 33, 45, 52, and 58). Here we present the results of a study of the efficacy and immunogenicity of the 9vHPV vaccine in women 16 to 26 years of age. METHODSWe performed a randomized, international, double-blind, phase 2b-3 study of the 9vHPV vaccine in 14,215 women. Participants received th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
405
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(427 citation statements)
references
References 22 publications
(43 reference statements)
11
405
1
10
Order By: Relevance
“…In a total of 14,215 randomized participants population the 9vHPV vaccine has been studied: this study showed that the 9vHPV vaccine prevented cervical, vulvar, and vaginal disease and persistent infection associated with HPV-31,-33,-45,-52, and-58, and generated antibody response to HPV-6,-11,-16, and-18 that was not inferior to that generated by the qHPV vaccine. The 9vHPV vaccine did not prevent infection and disease related to HPV types beyond the nine types covered by the vaccine (20).…”
Section: New Vaccine Against Hpv-diseasesmentioning
confidence: 92%
“…In a total of 14,215 randomized participants population the 9vHPV vaccine has been studied: this study showed that the 9vHPV vaccine prevented cervical, vulvar, and vaginal disease and persistent infection associated with HPV-31,-33,-45,-52, and-58, and generated antibody response to HPV-6,-11,-16, and-18 that was not inferior to that generated by the qHPV vaccine. The 9vHPV vaccine did not prevent infection and disease related to HPV types beyond the nine types covered by the vaccine (20).…”
Section: New Vaccine Against Hpv-diseasesmentioning
confidence: 92%
“…When compared to the quadrivalent HPV vaccine, the 9-valent vaccine prevented infection and disease specifically related to HPV -31, -33, -45, -52 and -58, and generated an equivalent antibody response to . This vaccine also holds the potential of markedly decreasing the incidence of abnormal cervical cytology and associated diagnostic and therapeutic procedures (Joura et al, 2015). This vaccine has the very high potential of markedly reducing the incidence of HPV-related pre-cancers and cancers when given at appropriate vaccination thresholds, which can contribute greatly to controlling cervical cancer in HIV+ women.…”
Section: Scc and Hivmentioning
confidence: 99%
“…At appropriate vaccination thresholds, this vaccine may have a tremendous impact on screening as well, with a legitimate rationale for increasing screening intervals given the anticipated decrease in the disease burden. Furthermore, understanding the specific prevalence and distribution of HPV genotypes in different geographic locations will help yield further insight into whether this new vaccine holds any promise and value (Joura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although advocated by the Centers for Disease Control and Prevention and the National Cancer Institute, the HPV quadrivalent and bivalent vaccine is largely underused in the U.S. in children, adolescents, and young adults [47]. The Food and Drug Administration has recently approved the nonavalent vaccine [48]. Its use will capture additional subtypes of HPV.…”
Section: Discussionmentioning
confidence: 99%